Verkehrssicherheit durch Fahrerassistenzsysteme. - Menzel, Christoph (Deutscher Verkehrs-Verl., 2004)
Das Auto ist seit jeher Technologieträger und Innovator. Nach und nach wurden dem Fahrer immer mehr Hilfestellungen geboten, um sein Automobil sicher und zuverlässig auf den Straßen bewegen zu können. Diese Hilfestellungen wurden dann im Laufe der Zeit komplexer und gegenseitig abhängig. So entstanden ganze Fahrerassistenzsysteme. difu

Advanced Driver's Assistance Systems (ADAS) facilitate driving tasks. In the late 1990s, ADAS overtake the vehicle mechanics in their importance towards driving performance. ADAS have different aims: On one hand traffic safety and political goals on the other hand economic goals of the automotive industry. This seems to be a contradiction. This contradiction is concise viewing the ISA-technology (Intelligent Speed Adaptation), which conduces to speed limit enforcement. Inappropriate speed is the most frequent accident reason. There are several research results on how ADAS effect on drivers. The technical status quo of ADAS longs for improvement. Nevertheless the compatibility of the various ADAS is high. Designing the "proper" human machine interface (HMI) has a high potential for traffic safety concerns. An intense cooperation between legislator, automotive industry and every other player in traffic safety will help to design flanking measures of law enforcement and ADAS features. difu
Keywords: Individualverkehr; Kraftfahrzeug; Straßenverkehr; Verkehrssicherheit; Informationstechnologie; Autofahrer; Fahrerassistenzsystem